(untitled) (Journal of Atomic and Molecular Sciences, 2021)
In present study an accurate ab initio potential energy curve of CH(X^2Π) has been determined at the complete basis set limit. The core-valence corrections and relativistic corrections including scalar relativity and spin-orbit coupling are determined. The vibrational and rotational levels are calculated based on fitted potential energy curve. Total 19 vibrational levels are found for ^13CH ground state, and comparing with available experimental data, the deviation is less than 15 cm^-1. The dissociation energy is calculated within 50 cm^-1 of the experimental value 29358 cm^-1. The A^2Δ - X^2Π electric transition dipole moment function is calculated, and the high-temperature fluorescence spectra arising from A^2Δ - X^2Π transition are simulated.